Education, human rights and social reconstruction in contemporary policies for schooling in Brazil - Dias da Silva, Rodrigo Manoel; Dias da Silva, Roberto Rafael (Revista Diálogo Educacional, 2013)
This paper aims at analysing the shaping of human rights as a key subject to make Brazilian policies for schooling in our time. From a sociological slant about different processes of individualisation in the contemporary society, the writers problematise the role the theme plays in the social agenda, and make a critique of different meanings it has in our time, emphasising on its strategic position towards new ways of managing school policies and processes. Finally, by looking at the renewing of human rights in documents made for basic education, they argue that these rights have been assumed as an important tool for school fairness, while creating narratives of social reconstruction for a society where uncertainty, flexibility and individualism are naturalised in collective processes of formation and living together.